RESTORATIVE JUSTICE AGAINST ARREST MARRIAGE PRACTICES AT THE WEST SUMBA POLICE - Thene, Rizal Simon (Veredas do Direito, 2025)
The Restorative Justice approach has increasingly attracted attention in criminal case resolution as it views crime as a violation of the rights of individuals/groups and of social relations, thereby requiring the offender to restore the harm caused. The phenomenon of “kawin tangkap” in customary communities in several regions, including West Sumba, presents a dilemma for the West Sumba Resort Police (Polres Sumba Barat): formal legal processes focused on criminal sanctions often fail to address the cultural and social dimensions of the communities involved. This study aims to analyze the possibilities and challenges of applying Restorative Justice to handle kawin tangkap cases in the Polres Sumba Barat jurisdiction and to formulate fair and sustainable solutions from legal and cultural perspectives. The research uses a juridical‑normative approach enriched by empirical data (normative–empirical). Data were collected from primary, secondary, and tertiary legal materials as well as relevant field sources. The results are expected to provide recommendations for a more inclusive, culturally sensitive, and practicable dispute resolution model for law enforcement and customary communities; the research output will include a scientific article intended for international publication.